(untitled) (Global Journal of Human-Social Science, 2016)
The study assessed the physical land suitability for cassava cultivation in southern part of Adamawa State using Multi-criteria evaluation and GIS technique. Within the study area, the production of cassava is mainly for food and there are only little opportunities for its commercial development. This therefore makes it necessary to carry out land suitability analysis in order to provide information on the study area that would guide in sustaining long term production of cassava. The environmental variables examined were Mean Annual rainfall, Mean Temperature, Length of rainfall, Relief and Soil which were obtained from the Upper Benue River Development Authority (UBRDA), Yola. The primary data were sourced by means of field survey to obtain the coordinates of the current cassava growing areas for mapping. The five factor maps were reclassified based on environmental requirement of cassava crop in the IDRISI Taiga environment and different weights were assigned to each factor to represent their relative importance using the pair-wise comparison Matrix.